Neurocysticercosis in Paraiba, northeast Brazil: an endemic area? Neurocisticercose na Paraíba, Nordeste do Brasil: uma área endêmica? - Thiago D. Gonçalves-Coêlho; Matheus D. G. Coêlho (Arquivos de Neuro-Psiquiatria)
Neurocysticercosis is the central nervous system infestation by Cysticercus cellulosae, the larval form of Taenia solium. It is related to poor hygiene habits and sanitation; although Northeast is poorest Region of Brazil, it has been always stated as a non-endemic area. After the installation of computed tomography (CT) service, the incidence of neurocysticercosis began to raise in neurology services in Campina Grande PB, a city where people from the interior Paraíba can find specialized medical facilities. We analyse 5,883 CT record of the TomoHPI Computed Tomography Service from August 1993 to December 1995, observing 1.02% suggestive neurocysticercosis cases and classified them according to sex and age, precedence and socioeconomic condition. Distribution of cases according to age is homogeneous until the age of 50 (mean: 28.36 years old). Men and women are equally affected. Urban areas inhabitants represented 83.33%. Residents of Campina Grande represented 48.33% and 48.34% were residents of cities around Campina Grande (until 50 Km around) and other cities of Paraíba State. Fifty-eight patients were dependent to public health care system. We conclude that neurocysticercosis seems to be endemic in Paraíba State, demanding a more detailed study to determine its incidence/prevalence. Neurocisticercose é a infestação do sistema nervoso central pelo Cysticercus cellulosae, a forma larval da Taenia solium. É relacionada a hábitos higiênicos e sanitários precários; embora o Nordeste seja a Região mais pobre do Brasil, foi sempre considerada área não-endêmica para neurocisticercose. Depois da instalação de um serviço de tomografia computadorizada (TC), a incidência da neurocisticercose começou a crescer nos serviços de neurologia em Campina Grande PB, cidade para onde confluem pessoas de todo o interior paraibano à procura de serviços médicos especializados. Analisamos 5.883 TC realizadas no Serviço TomoHPI de Radioimagem do Hospital Pedro I de agosto de 1993 até dezembro de 1995 e 1,02% foram diagnosticadas como sugestivas de neurocisticercose e classificadas de acordo com idade e sexo, procedência e condições sócio-econômicas. A distribuição dos casos de acordo com a idade é homogênea até os 50 anos de idade (média: 28,36 anos). Homens e mulheres são afetados igualmente. Procedentes de áreas urbanas representam 83.33%. Residentes em Campina Grande representam 48.33% do total; 48,34% residem em cidades ao redor de Campina Grande (até 50 Km de distância) ou em outras cidades da Paraíba. Cincoenta e oito pacientes são dependentes do Sistema Único de Saúde. Concluimos que a neurocisticercose parece ser endêmica em nosso Estado, sendo necessários estudos mais detalhados para que tal assertiva possa ser confirmada.